Pengaruh Strategi Pembelajaran RAFT (Role, Audience, Format, Topic) Terhadap Kemampuan Menulis Teks Eksplanasi Kelas VIII SMP Swasta GKPS 3 Pematangsiantar - Diera Elika Purba; Fitriani Lubis (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to (1) analyze the skills of class VIII students of GKPS 3 Pematangsiantar Private Middle School in compiling explanatory texts before the implementation of the RAFT strategy. (2) Analyze the skills of class VIII students of GKPS 3 Pematangsiantar Private Middle School in compiling explanatory texts after the implementation of the strategy. (3) Analyze the impact of the RAFT learning strategy on the skills of compiling explanatory texts of class VIII students of GKPS 3 Pematangsiantar Private Middle School. The population in this study were class VIII students of GKPS 3 Pematangsiantar Private Middle School, namely class I with 26 students and class II with 27 students. The method used in this study was a two-group posttest design. Analysis assumption tests, normality tests and hypothesis tests were used in data analysis. The results of the study in the control class reached an average of 69.5 and were included in the "sufficient" category. The results of the study obtained with the RAFT strategy were 86.03 and were included in the "very good" category. Through the hypothesis test, namely tituing>ttable, namely 7.109>1.67528, it can be concluded that there is a significant influence of the use of the RAFT strategy on the ability to write explanatory texts of Class VIII students of SMP Swasta GKPS 3 Pematangsiantar.